Ensuring Availability and Quality of Research Data through Open Access and Public Peer-Review - Rasmussen, Martin (Septentrio Conference Series, 2014)
The scientific and economic value of research data is enormous. In order to realize a successful subsequent usage, the scientific community needs efficient access to data. Thereby, the access has to be reliable and persistent. In addition, the quality of the data has to be proved following standardized work flows. One solution to these preconditions is to apply techniques of today’s scientific publishing to research data. Besides the access to the data sets through data repositories together with some metadata, the data should undergo a transparent peer-review using a publication platform. The presentation discusses two approaches. On the one hand, the data can be the basis for a research article and undergoes a review parallel to the review of the manuscript. The data is then a reviewed supplement to a scientific publication. On the other hand, the data itself can be the subject of a publication whose quality is then assured by peers. The presentation provides practical experience, especially with the latter strategy, realized through the open access journal Earth System Science Data (ESSD) with interactive public peer-review.